Le marché immobilier : quelques perspectives à long terme pour la région de Trois-Rivières - Farrell, L. (L'Actualité économique)

(untitled) (HEC Montréal, 1983)
AbstractThe results of any analysis of local real estate markets must be qualified interms of the long run equilibrium conditions assumed in the study. Such propertycharacteristics as: non homogeneity, durability, length of response lag time, etc.,are frequently suggested as major factors which contribute to the inefficiency ofreal estate markets. Periods of prolonged exogeneous inflationary expectations,which may be indicated by changes in the Consumer Price Index (CPI), addfurther complexity to the analysis of real estate markets.This paper presents a brief discussion of the factors which influence thesupply and demand for Real Estate. Special reference is made to the City ofTrois-Rivières, Québec, which is analysed over the ten year period 1971 to 1981. In this market the impact of changes in income on long run demand would appearto be negative. The effect of demographic factors, particularly population in the25 to 34 year age group, is not clear. There is some indication of a shift in supplyacross submarkets over the 1976-1979 time period.Price changes, measured in current dollars using the Multiple Listing Service(MLS) average transaction price, increased approximately 200 per cent over arelatively short period in the early 1970s. Most of this appreciation appears tohave been lost over the longer time period of the study.Average MLS transaction price, adjusted for inflation, fluctuated between$12,000 and $28,000 over the same period.After appropriate qualification of the results, in terms of the data and themethodology used to analyse the data, it would appear that housing prices in theaggregated Trois-Rivières market have not increased appreciably in current orconstant dollars over the period 1971-1981 although this may not have been thecase in particular submarkets.